The Diversity of Butterflies in Narmada Park, West Lombok Regency - Mirnawati, Mirnawati; Muhlis, Muhlis; Ilhamdi, Mohammad Liwa (Jurnal Biologi Tropis, 2025)
One of Indonesia’s biodiversity components is the insect group. Insects (Insecta) represent the largest group of animals, accounting for about one-quarter of all known animal species on Earth. Among them, beetles and butterflies are the most diverse, largely influenced by the availability of host plants as an energy source. This study aimed to determine the diversity, dominance, and evenness of butterfly species in Narmada Park, West Lombok Regency, and to explore their potential as enrichment material for Animal Ecology practicum. The research was conducted at two observation sites one dominated by flowering plants and the other by trees using a survey method with purposive sampling and a sweeping net technique. The results recorded 122 butterfly individuals comprising 13 species from four families: Nymphalidae, Lycaenidae, Papilionidae, and Pieridae. The Shannon-Wiener diversity index (H’) was 2.50937 (moderate category), Simpson’s dominance index (D) was 0.085595, and Pielou’s evenness index (E) was 0.978331. The measured environmental factors included temperature (31.7°C), humidity (67.5%), and light intensity (385 Cd). The moderate diversity and high evenness indicate a relatively stable habitat condition that supports the existence of butterflies in the area.